Soft X-ray tomography reveals variations in B.subtilis biofilm structure upon tasA deletion [data] - Weinhardt, Venera; Chatzimpinou, Anthoula; Diehl, Anne; Harhoff, A. Tobias; Driller, Kristina; Vanslembrouck, Bieke; Chen, Jian-Hua; Kairišs, Kristaps; Loconte, Valentina; Le Gros, Mark A.; Larabell, Carolyn; Turgay, Kürsad; et al. (Universität, 2025)
Bacterial biofilms are complex communities of cells within a self-produced extracellular matrix. They play crucial roles in healthcare, nutrition, agriculture and environmental research, yet an analysis of their elaborate 3D architecture remains challenging. In our work, we developed a “biofilm-in-capillary” growth method compatible with full-rotation soft X-ray tomography, providing high-resolution 3D imaging of bacterial cells and their surrounding extracellular matrix during biofilm formation, without drying or fixation steps. These datasets are reconstructed 3D volumes obtained by soft X-ray tomography of WT and ΔtasA mutants, including rescue with TasA protein. The data is organized in individual *.tif files with prefixes as follows: for single-cell suspension WT "Diehl_Biofilm_Bacillus_subtilis_WT_GFP_0h_10797"; for single-cell suspension ΔtasA mutants "Diehl_Biofilm_Bacillus_subtilis_tasA_GFP_0h_10801_"; for WT biofilm formed after 22h "Diehl_Biofilm_Bacillus_subtilis_WT_GFP_10479";for ΔtasA biofilm formed after 22h "Diehl_Biofilm_Bacillus_subtilis_tasA_GFP_10517";for ΔtasA biofilm formed after 44h "Diehl_Biofilm_Bacillus_subtilis_tasA_GFP_ctrl_44h_10815";for ΔtasA biofilm with the addition of TasA protein formed after 44h "Diehl_Biofilm_Bacillus_subtilis_tasA_GFP_rescue_44h_10821"
Gesehen am 05.02.2025
Keywords: Forschungsdaten; Datenbank